O-27 Rehabilitation provision across uk hospice services. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Fettes, Lucy; Talbot-Rice, Helena; Preston, Gail; Wilkinson, Alanah; Murtagh, Fliss EM; Higginson, Irene J; Turner-Stokes, Lynne; Ashford, Stephen; Maddocks, Matthew
Abstract : Background: Rehabilitation is a key component of multi-professional palliative care. The provision of rehabilitation across hospice services falls outside national audit and is under-researched and therefore poorly understood. Aim: To describe the therapy input and interventions provided to patients attending UK hospice rehabilitation services, across inpatient and outpatient settings. Methods: Adults with advanced progressive disease were recruited to a multisite observational study examining the use of goal setting in routine rehabilitation practice, across 10 nationally representative hospices. Baseline demographics, allied health professional (AHP) involvement and therapy interventions were recorded, then compared according to setting using chi-squared or Mann Whitney U tests as appropriate. Therapy interventions were ranked for each setting. Results: 239 patients (46% male, mean (SD) age 68 (15) years) from outpatient (n=141) and inpatient (n-98) settings took part. The majority (72%) had a primary cancer diagnosis and a stable phase of illness (70%). Inpatients received more therapy input compared to outpatients with a greater number of AHPs involved (median [IQR] 2 [1–3] vs. 1 [1–2], p<0.001), more frequent involvement from occupational therapists (56% vs. 27%, p<0.001) and rehabilitation assistants (51% vs. 30%, p=0.001), and more therapy interventions being provided during an episode of care (median [IQR] 4 [2–6] vs. 2 [1–4], p<0.001). The type of therapy intervention(s) also differed according to setting (Table 1). Conclusion: Within UK hospice rehabilitation services, greater therapy input is typically provided to inpatients as compared to outpatients within each episode of care. The type of therapy intervention also appears to be setting dependant, with inpatient therapy focusing on basic mobility and other functional tasks and outpatient therapy on exercise and supported self-management.